Penerapan Shariah Compliance Pada Manajemen Risiko Produk Mikro Ekspress Berbasis Akad Murabahah (Studi Kasus BPRS Mandiri Mitra Sukses Gresik) - Ahmad, Resha; Setiyowati, Arin; Huda, Fatkur (ITB AAS INDONESIA Surakarta, 2024)
In recent years, the Islamic finance industry has experienced rapid growth, significantly impacting the global economy. One Islamic financial institution that has grown rapidly as the banking system has declined is BPRS. BPRS, as an Islamic microfinance institution operating in the lower economic zone, has many enthusiasts due to its focus on microfinance based on sharia principles. BPRS Mandiri Mitra Sukses Gresik, which focuses on community economic empowerment, offers the Micro Express product based on the akad murabahah as one of the main pillars in its service portfolio. However, with the ever-changing economic dynamics and increasingly stringent sharia regulations, BPRS Mandiri Mitra Sukses Gresik needs to evaluate risk management on this product to ensure compliance with sharia principles. This research will help explain the risk management steps taken by BPRS Mandiri Mitra Sukses Gresik on the Micro Express product based on the akad Murabahah and analyze the compliance of Shariah compliance with the risk management of the Micro Express product based on the akad Murabahah at BPRS Mandiri Mitra Sukses Gresik. This research is qualitative research with a case study approach, focusing on the description of the risk management mechanism applied at BPRS Mandiri Mitra Sukses Gresik and the analysis of the compliance of risk management with sharia compliance on the Micro Express product based on the murabahah contract. The aim of this research is to determine the steps and compliance of Shariah compliance in the risk management taken by BPRS Mandiri Mitra Sukses Gresik on the Micro Express product based on the akad Murabahah. The result is that the implementation of risk management on the Micro Express product based on the akad murabahah at BPRS Mandiri Mitra Sukses Gresik is in accordance with DSN MUI Fatwa No.04/DSN-MUI/IV/2000 regarding Postponement of Murabahah Financing, Financial Services Authority Regulation No.23/POJK.03/2018 regarding the Implementation of Risk Management for Islamic Rural Banks, and sharia principles in UU RI No.21 Tahun 2008 Pasal 2 regarding the fulfillment of sharia principles.